O składni wypracowań gimnazjalistów (na podstawie wybranych prac pisemnych) - Lewicka, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article presents the idiosyncrasies of the frequency of syntactic structures used by secondary school students (aged 13-15). It is drawn on the basis of research carried out in a secondary school in Kalisz. A total of 4,021 syntactic structures from 276 compositions written by students from two classes were analysed in order to present phenomena typical of the ultimate syntactic structures. The data was collected for two school years (2011/2012 and 2012/2013) and indicates the most frequently and generally used syntactic structures as well as the less popular and more specific ones. In addition, a comparison of the results and transposing them to a timeframe makes it possible to present the evolution in the syntax of compositions written by secondary school students. An analysis of the material has also led to specifying the types of syntactic errors and their frequency.